2017
DOI: 10.1136/acupmed-2015-010854
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Irritable Bowel Syndrome: 2-Year Follow-Up of a Randomised Controlled Trial

Abstract: BackgroundA recent randomised controlled trial (RCT) of acupuncture as a treatment for irritable bowel syndrome (IBS) demonstrated sustained benefits over a period of 12 months post-randomisation.AimTo extend the trial follow-up to evaluate the effects of acupuncture at 24 months post-randomisation.MethodsPatients in primary care with ongoing IBS were recruited to a two-arm pragmatic RCT of acupuncture for IBS. Participants were randomised to the offer of up to 10 weekly sessions of acupuncture plus usual care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Overall, 11 patients with IBS‐D or functional diarrhoea reported 11 AEs: insomnia (n = 4), fainting (n = 3), abdominal pain (n = 1), cold limbs (n = 1), and weakness (n = 1) with electroacupuncture; and hot flush (n = 1) with loperamide . However, one study found that improvements in IBS symptoms observed with acupuncture at 3 months were sustained for up to 2 years, although there was no difference between acupuncture and usual care; follow‐up data were available for 61% of study participants at 2 years . Number needed to treat and number needed to harm values for acupuncture as an IBS treatment modality have not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 11 patients with IBS‐D or functional diarrhoea reported 11 AEs: insomnia (n = 4), fainting (n = 3), abdominal pain (n = 1), cold limbs (n = 1), and weakness (n = 1) with electroacupuncture; and hot flush (n = 1) with loperamide . However, one study found that improvements in IBS symptoms observed with acupuncture at 3 months were sustained for up to 2 years, although there was no difference between acupuncture and usual care; follow‐up data were available for 61% of study participants at 2 years . Number needed to treat and number needed to harm values for acupuncture as an IBS treatment modality have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…96 However, one study found that improvements in IBS symptoms observed with acupuncture at 3 months were sustained for up to 2 years, although there was no difference between acupuncture and usual care; followup data were available for 61% of study participants at 2 years. 99 Number needed to treat and number needed to harm values for acupuncture as an IBS treatment modality have not been reported.…”
Section: Mechanical Interventionsmentioning
confidence: 99%
“…The currently used medical treatments can improve intestinal motility and thereby improve the patient's quality of life, but they do not improve the contraction and relaxation of intestinal muscles, and are also associated with adverse side effects . In clinical practice, acupuncture is accepted as an alternative potentially effective therapy for constipation, irritable bowel syndrome and other diseases . It is believed that specific acupoints are associated with certain regional effects .…”
Section: Introductionmentioning
confidence: 99%
“…4 In clinical practice, acupuncture is accepted as an alternative potentially effective therapy for constipation, irritable bowel syndrome and other diseases. [5][6][7] It is believed that specific acupoints are associated with certain regional effects. 8 In the case of gastrointestinal dysfunction, ST 25 (tianshu) and ST 37 (shangjuxu) are the most commonly used acupoints for treatment.…”
mentioning
confidence: 99%
“…Many behavioral studies have confirmed that EA stimulation exerts good effects on rats with acute or chronic visceral hyperalgesia ( Qi and Li, 2012 ; Wang et al, 2012 ). In addition, EA therapy has been proven to be effective in treating visceral pain in long–term follow–up clinical trials ( MacPherson et al, 2017 ). It is generally accepted that EA analgesia is an integrative process of afferent impulses between pain regions and acupoints at convergence neurons and this process involves different levels of central structures, such as spinal dorsal horn ( Rong et al, 2005 ), nucleus tractus solitarius ( Liu et al, 2014 ) and periaqueductal gray ( Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%